Evaluation of academic finance conferences - Kerl, Alexander; Miersch, Enrico; Walter, Andreas (Journal of Banking & Finance, 2018)
We develop a novel framework to evaluate the quality of academic finance conferences. In particular, we analyze the publication and citation outcomes of 18,535 conference papers presented at 15 academic finance conferences between 2007 and 2012. In addition, we provide evidence of the perceived quality of these academic finance conferences by surveying a large number of participants of the 15 conferences. The use of three different quality proxies enables us to contrast levels of conference quality based on the quality of presented papers to levels of conference quality perceived by conference participants. Our results reveal two quality clusters of academic finance conferences and show that the use of the three quality dimensions, while generally robust, is associated with a number of peculiarities.